Influence of Leadership Style, and Organizational Culture Towards Organizational Citizenship Behavior Through Job Satisfaction as an Intervening Variable - Muhammad Zhulali Nauli; Dudung Hadiwijaya; Priyo Susilo (PT Mattawang Mediatama Solution, 2024)
The purpose of this investigation is to determine the influence of Organisational Culture and Leadership Style on OCB, with job satisfaction serving as an intervening variable. The data collection procedure utilises a purposive sampling type with a non-probability sampling technique, and this research employs a quantitative-associative approach. The Directorate General of Customs and Excise employs a Google Forms questionnaire to distribute data to its personnel. The software Smart-PLS is employed to evaluate the reliability of PLS-SEM-based models. The results of the Structural Equation Modelling (SEM) analysis and hypothesis testing conducted in this study were used to derive conclusions. Organisational Culture and Leadership Style have a beneficial effect on OCB and Job Satisfaction, as evidenced by the results of the investigations that have been conducted. Additionally, Leadership Style has a substantial indirect impact on Job Satisfaction, which in turn affects OCB. As an outcome of organisational culture, job satisfaction has an insignificant indirect effect on OCB.